The Effect of Dividend Policy and Capital Structure on Firm Value With Corporate Social Responsibility as A Moderating Variable in Companies Listed on The Jakarta Islamic Index - Silviani Ayudia; Nagian Toni; Yeni Ariesa; Wiliam Wiliam (CV. Aksara Global Akademia, 2024)
This study aims to determine the effect of dividend policy, and capital structure on firm value in companies listed on the Jakarta Islamic Index with corporate social responsibility as a moderating variable. The research design used is the casual design method. The population used in this study were companies listed on the Jakarta Islamic Index for the 2019-2021 period. purposive sampling technique was used in sampling so that 41 companies were obtained by analyzing data as many as 123 samples. The data analysis technique used is panel data analysis using the E-views program. The results showed that dividend policy has a positive and insignificant effect on firm value, capital structure has a negative and significant effect on firm value, corporate social responsibility cannot moderate the effect of dividend policy on firm value, corporate social responsibility can moderate the effect of capital structure on firm value.